2014
DOI: 10.1186/preaccept-1329924074106331
|View full text |Cite
|
Sign up to set email alerts
|

Investigations by Raman microscopy, ESEM and FTIR-ATR of wall paintings from Qasr el-Ghuieta temple, Kharga Oasis, Egypt

Abstract: In the present work, a multi-analytical approach was used to analyze samples collected from the wall paintings of Qasr el-Ghuieta temple, Kharga Oasis, Egypt. The temple is dating back to the 27th dynasty (525-404 BC) and was completed during the Ptolemaic period. The samples were analyzed by optical microscopy (OM), environmental scanning electron microscopy (ESEM) coupled with an energy dispersive X-ray analysis system (EDX), Raman microscopy and Fourier transform infrared-attenuated total reflectance spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…It can be observed that the peaks at 790 and 679 cm -1 are most probably due to symmetric stretching of Si-O of kaolinite and quartz [49,50]. Peak at 522 cm -1 matches to that of Si-O-Al of kaolinite and quartz [48]. The peak at 452 cm -1 is assigned as Si-O-Al stretching vibration of kaolinite [50], while the band at 409 cm -1 in spectrum shows the presence of Si-OH wagging mode of silica [49].…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…It can be observed that the peaks at 790 and 679 cm -1 are most probably due to symmetric stretching of Si-O of kaolinite and quartz [49,50]. Peak at 522 cm -1 matches to that of Si-O-Al of kaolinite and quartz [48]. The peak at 452 cm -1 is assigned as Si-O-Al stretching vibration of kaolinite [50], while the band at 409 cm -1 in spectrum shows the presence of Si-OH wagging mode of silica [49].…”
Section: Resultsmentioning
confidence: 92%
“…The peaks at 1543 and 1458 cm -1 could be due to bending vibration of water molecules of silica [49]. The peak at 998 cm -1 is probably due to Si-O-Al stretching vibration, while at 910 cm -1 may indicate the presence of Al-O-H stretching vibration of kaolinite and red ochre [48]. It can be observed that the peaks at 790 and 679 cm -1 are most probably due to symmetric stretching of Si-O of kaolinite and quartz [49,50].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…By comparing the functional groups of animal glue standard samples with the results of sample (3) of the used material in the adhesion and the reassembly of the mask, it became obvious that animal glue had been used to reassemble the studied mask. Also, comparing the functional groups of sample (1D) of the intact stucco sample proves that the stucco sample consists mainly of gypsum as a binding material [18][19][20] (Table 3 and Fig. 6).…”
Section: Ftir Analysismentioning
confidence: 99%
“…Besides that, there was little scienti c analysis and research on the paint layers of arhat statues of Lingyan Temple. Complementary and multiple analytical techniques are widely used in the study of paint layers of painted cultural relics such as polychrome statues [4][5][6][7], mural paintings [8][9][10][11], painted pottery [12][13] and so on, which can successfully reveal the microscopic structure of paint layers, the composition of the pigment and the priming layers, the types of binding media found in paint layers, repair materials, and the paint stratigraphy. In this paper, multiple analytical techniques including ultra depth of eld 3D microscopy (OM), Micro-Raman spectroscopy (μ-RS), scanning electron microscopy coupled with energy dispersive X-ray analysis (SEM-EDS) and Fourier transform infrared spectroscopy (FTIR) were selected to analyze the paint layers from the Bodhidharma statue.…”
Section: Introductionmentioning
confidence: 99%